O papel das novas tecnologias de informação e comunicação na superação dos obstáculos à concretização da democracia participativa no Brasil - Monteiro, Maurício Gentil (2018)
Participative democracy is an unrealized constitutional promise, given, among other reasons, the following obstacles: the blocking of the representative system to the use of plebiscites and referendums, as well as the introduction of new mechanisms of direct democracy, the oligopoly of media and the control of public debate by economic power and education that does not effectively prepare for the exercise of citizenship. However, from the rapid growth and rapid expansion of the Internet and, consequently, the development of new information and communication technologies, which together make up what is now known as cyberspace and its effective cyberdemocratic practice, with the possibility that any person can express himself freely and in quick connectivity with the world - without needing the filter of the government or the traditional means of social communication (television and radio) - through the mechanisms provided by the advent of the internet, transformed personal relationships, professional relations, power relations and the form of personal and social-community interconnection with the world. In politics, NICT began to be used as a result of the occupation of cyberspace and activism and digital activism, which came to a surprising extent to astonish the world with the various social mobilizations that were practiced in a new format, mainly starting in 2010 , in movements such as the "Arab Spring", movements in Greece in 2011/2012, in Spain in 2011, the Occupy Wall Street movement in 2011, even in Brazil, the so-called "June Journeys" 2013, broad popular mobilizations that had in the NITC its main instrument of convocation, call and agglutination. As in Brazil, unlike what happens in liberal democracies with a well-established civic culture, where participatory democracy and the instruments of popular participation in the democratic process are constant, participatory democracy is still far from being put into real political practice, the scientific opportunity to investigate the potential of NICT in the implementation of participatory democracy appeared more strongly and became the object of the present thesis.